2019
DOI: 10.1111/1460-6984.12457
|View full text |Cite
|
Sign up to set email alerts
|

Assessing voice health using smartphones: bias and random error of acoustic voice parameters captured by different smartphone types

Abstract: Background Occupational voice problems constitute a serious public health issue with substantial financial and human consequences for society. Modern mobile technologies such as smartphones have the potential to enhance approaches to prevention and management of voice problems. This paper addresses an important aspect of smartphone‐assisted voice care: the reliability of smartphone‐based acoustic analysis for voice health state monitoring. Aim To assess the reliability of acoustic parameter extraction for a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 24 publications
2
36
0
11
Order By: Relevance
“…The study by [7] therefore suggests that smartphone reliability for acoustic voice assessment very much depends on the parameter under question. The study presented here is a continuation study of [7], extending the analysis to the quantification of added noise and glottal pulse efficiency as reflected in the spectral tilt of the voice spectrum.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…The study by [7] therefore suggests that smartphone reliability for acoustic voice assessment very much depends on the parameter under question. The study presented here is a continuation study of [7], extending the analysis to the quantification of added noise and glottal pulse efficiency as reflected in the spectral tilt of the voice spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…Smartphones are increasingly used to collect speech data for acoustic analysis, and several authors have suggested that smartphones have sufficient reliability for voice analysis with a clinical purpose [1]- [6]. [7] took a less optimistic stance on this and argued that previous analyses partly rested on false assumptions about the nature of the problem. For example, some studies have used non-significance between a smartphone recording and a reference recording as evidence that smartphone measurement are reliable.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations